Enhanced Mid‐depth Southward Transport in the Northeast Atlantic at the Last Glacial Maximum Despite a Weaker AMOC. Issue 2 (5th February 2020) - Menviel, L. C.; Spence, P.; Skinner, L. C.; Tachikawa, K.; Friedrich, T.; Missiaen, L.; Yu, J.
Abstract: While previous studies consistently suggest that North Atlantic Deep Water (NADW) was shallower at the Last Glacial Maximum (LGM) than at pre‐industrial, its strength is still controversial. Here, using a series of LGM experiments, we show that proxy records are consistent with a shallower and ∼ 50% weaker NADW, associated with a ∼ 3° equatorward shift of the sea ice edge and convection sites in the Norwegian Sea. A shoaling and weakening of NADW further allow penetration of Antarctic Bottom Water in the North Atlantic, despite Antarctic Bottom Water transport being reduced by ∼ 40%. While the Deep Western Boundary Current in the northwest Atlantic weakens with NADW, the mid‐depth southward flow on the east side of the north Mid‐Atlantic Ridge strengthens, consistent with paleorecords. This northeast Atlantic intensification is due to a change in density gradients: a weaker AMOC reduces the transport of equatorial waters to the northeast Atlantic, thus weakening the North Atlantic zonal density gradient. The resultant globally weaker oceanic circulation at the LGM would have contributed to an increase in oceanic carbon content and thus a decrease in atmospheric CO 2 concentration. Key Points: As the AMOC weakens, Nordic Sea sea ice and convection sites shift equatorward and the Deep Western Boundary Current weakens proportionally As the AMOC weakens, the southward flow on the eastern side of the Mid‐Atlantic Ridge strengthens by up to 100% Proxy records are consistent with both weaker NADW and AABW at the Last Glacial Maximum